Aplicación del modelo Registros Continuum en una universidad pública - Viana, Gilberto Fladimar Rodrigues [UNESP]; De Carvalho Madio, Telma Campanha [UNESP] (My University, 2016)
The Records Continuum (RC) model is applied to a database created in 1992, called Education Information System, in the Project Registration module of the Federal University of Santa Maria (UFSM), located in Santa Maria, in the state of Rio Grande do Sul. The four dimensions considered in the RC diagram are applied, also considering the cautions established in the Brazilian Access to Information Law.
Applying the Records Continuum model in a public university
Keywords: Academic archives; Access to information law; Digital archives; Document management model; Federal University of Santa Maria (Brazil); Records continuum